Relationship between complete dentures and swallowing ability - Mohamad Zaid Novialdi; Muslita Indrasari (Indonesian Journal of Prosthodontic, 2023)
The aging process causes changes in the anatomical structures of the oral cavity and pharynx that are closely re-lated to the ability to chew and swallow. The use of a complete denture may prevent this to happen, but a lower mastication pressure is visible in complete dentures compared to natural teeth. This may have an impact on swal-lowing ability. In general, a complete denture improves the swallowing process and prevents oral cavity and pha-rynx changes. Several factors, such as denture thickness, the interaction of oral musculatures with the denture, and occlusal contacts will affect the effectiveness of the swallowing process. A proper and stable denture will improve the pharyngeal movement involved in swallowing, thus avoiding airway obstructions. It is concluded that the use of a proper complete denture is important as all four phases of the normal swallowing process are affected by the den-ture. Untreated edentulous jaws may cause oropharyngeal expansion which increases the risk of food bolus pene-tration into the hypopharynx and ultimately delay the pharyngeal swallowing process